Zirconium and hafnium (1-pyridinio)imido complexes: functionalized terminal hydrazinediido analogues : dedicated to Professor Brian F.G. Johnson on the occasion of his 70th birthday - Herrmann, Heike; Gehrmann, Thorsten; Wadepohl, Hubert; Gade, Lutz H. (Dalton transactions, 2008)
Reaction of the diamidozirconium complex [Zr(N2TBSNpy)(NMe2)2] (1) (N2TBSNpy = CH3C(C5H4N)(CH2NSiMe2tBu)2) or the diamidohafnium complex [Hf(N2TBSNpy)(NMe2)2] (2) with one molar equiv. of 1-aminopyridinium triflate in the presence of one equiv. of pyridine gave the corresponding (1-pyridinio)imido complexes [Zr(N2TBSNpy)(N-NC5H5)(OTf)(py)] (3) and [Hf(N2TBSNpy)(N-NC5H5)(OTf)(py)] (4). These were converted to the acetylide complexes [Zr(N2TBSNpy)(N-NC5H5)(CCPh)(py)] (5) and [Hf(N2TBSNpy)(N-NC5H5)(CCPh)(py)] (6) by reaction with lithium phenylacetylide and substitution of the triflato ligand. Upon reaction of 3 and 4 with one molar equivalent of R-NC (R = tBu, Cy, 2,6-xyl), N-N bond cleavage in the (1-pyridinio)imido unit took place and the respective carbodiimido complexes [M(N2TBSNpy](NCNR)(OTf)(py)] (7-12) were formed instantaneously. A similar type of reaction with CO gave the isocyanato complex [Zr(N2TBSNpy](NCO)(OTf)(py)] (13). Finally, the abstraction of the pyridine ligand in compounds 3 and 4 with B(C6F5)3 led to the formation of the triflato-bridged dinuclear complexes [Zr(N2TBSNpy)(N-NC5H5)(OTf)]2 (14) and [Hf(N2TBSNpy)(N-NC5H5)(OTf)]2 (15).
CCDC reference numbers 679492–679494 and 687175–687177. For crystallographic data in CIF or other electronic format see DOI: 10.1039/b807808d
Gesehen am 13.12.2022
Keywords: Festschrift